(untitled) (JURNAL ADMINISTRASI PUBLIK, 2022)
The purpose of this study was to find out how the community’s satisfaction with the beach reclamation policy in the Malalayang area, Manado City. This study uses descriptive qualitative research methods. Community satisfaction with the coastal reclamation policy can be seen through the relationship between the results in the field and what the community previously hoped for. There are 3 indicators to measure community satisfaction, namely perceived quality, perceived value, and service user expectations. Based on the results of the study that community satisfaction with the beach reclamation policy in the Malalayang area of Manado City for the perceived quality it can be said to be quite good, but the government no longer pays attention to the shoulder reclamation area which has resulted in some being neglected and uncontrolled. Meanwhile, the perceived value of this beach reclamation policy has not been fulfilled properly because the impact of losses that the community feels is more and greater than the benefits of this beach reclamation. And the last is the expectation of service users to improve, control and provide assistance to coastal communities. Keywords : Community Satisfaction, Public Policy, Coastal Reclamation